DETERMINANTS OF ECONOMY AND HUMAN DEVELOPMENT: A DECADE OF PROVINCES IN INDONESIA - Parwangsa, Baiq Dwi Indar; Fadliyanti, Luluk; Anggara, Jaka (Quantitative Economics Journal, 2024)
ABSTRACT This study investigates how various factors affect the Human Development Index (HDI) across Indonesian provinces. It analyzes data from 30 provinces between 2013 and 2022, examining the influence of infrastructure, economic well-being (GRDP per capita), access to clean water and electricity, and unemployment and poverty rates. To account for overlapping factors, the research employs panel data regression with specific techniques to address multicollinearity. The results show that infrastructure investment and economic growth (GRDP per capita) significantly improve provincial HDI. This underlines the importance of prioritizing infrastructure development and inclusive economic strategies to achieve a better overall quality of life for Indonesians. Keywords: Human Development Index, Infrastructure, Indonesia, Ordinary Least Squares, Principal Component Analysis.